Kemampuan Pemecahan Masalah Mahasiswa PGSD pada Sistem Pertidaksamaaan Linear Dua Variable berdasarkan Taksonomi SOLO - Wulida Arina Najwa (Jurnal Pena Karakter : Jurnal Pendidikan Anak dan Karakter, 2019)
Problem solving is one of the objectives of learning mathematics. Not only for school students but also college student, especially PGSD students. The level of students' ability to solve problems can be seen using SOLO taxonomy. Using the SOLO taxonomy, the quality of students' answers to a problem can be analyzed based on the complexity of understanding. SOLO's taxonomy consists of 5 levels, namely (1) Pre-Structural Level, (2) Uni-Structural Level, (3) Multi-Structural Level, (4) Relational Level, (5) Expanded Abstract Level. This study uses qualitative research that describes the ability to solve the problem-solving linear inequality system of two variables in PGSD students using SOLO taxonomy. The results of this study indicate that the ability of PGSD students to solve problem solving problems varies. From the five SOLO taxonomic levels, there are PGSD students who meet levels 2 to 5, namely the Uni-Structural Level, Multi-Structural Level, Relational Level, Expanded Abstract Level. There are no students who meet level 1 in the SOLO taxonomy namely Pre-Structural Level.